THE ROLE OF DEONTIC MODALITY IN ENGLISH AND UZBEK BUSINESS DISCOURSE - Qodirova Mukaddas Tog‘ayevna (Web of Journals Publishing, 2024)
This article examines the role of deontic modality in English and Uzbek business discourse, focusing on the expression of obligations, permissions, prohibitions, and recommendations. Through comparative and lexical-semantic analysis, the study highlights how deontic modals are utilized in business communication within both languages, reflecting their distinct cultural approaches. English business discourse is marked by a higher degree of formality and strictness, particularly in the use of obligation and prohibition modals. In contrast, Uzbek discourse emphasizes politeness and respect, favoring permission and recommendation modals. The findings reveal the significant role deontic modality plays in shaping effective communication and strategies in business contexts.
Keywords: deontic modality, business discourse, obligation, permission, prohibition, recommendation.